The pathogenic LRRK2 R1441C mutation induces specific deficits modeling the prodromal phase of Parkinson's disease in the mouse - F. Giesert; L. Glasl; A. Zimprich; L. Ernst; G. Piccoli; C. Stautner; J. Zerle; S.M. Hölter; D.M. Vogt Weisenhorn; W. Wurst (Neurobiology of Disease, 2017)
The aim of the present study was to further explore the in vivo function of the Leucine-rich repeat kinase 2 (LRRK2)-gene, which is mutated in certain familial forms of Parkinson's disease (PD). We generated a mouse model harboring the disease-associated point mutation R1441C in the GTPase domain of the endogenous murine LRRK2 gene (LRRK2 R1441C line) and performed a comprehensive analysis of these animals throughout lifespan in comparison with an existing knockdown line of LRRK2 (LRRK2 knockdown line). Animals of both lines do not exhibit severe motor dysfunction or pathological signs of neurodegeneration neither at young nor old age. However, at old age the homozygous LRRK2 R1441C animals exhibit clear phenotypes related to the prodromal phase of PD such as impairments in fine motor tasks, gait, and olfaction. These phenotypes are only marginally observable in the LRRK2 knockdown animals, possibly due to activation of compensatory mechanisms as suggested by in vitro studies of synaptic transmission. Thus, at the organismal level the LRRK2 R1441C mutation does not emerge as a loss of function of the protein, but induces mutation specific deficits. Furthermore, judged by the phenotypes presented, the LRRK2-R1441C knock-in line is a valid preclinical model for the prodromal phase of PD.